Vascular endothelial growth factor (VEGF) receptor expression correlates with histologic grade and stage of colorectal cancer - Ali F. Hashim; As'ad A. Al-Janabi; Liwaa H. Mahdi; Kaswer M. Al-Toriahi; Akeel A. Yasseen (Libyan Journal of Medicine, 2010)
Background: Colorectal carcinoma (CRC) is the seventh-most common malignancy and is the main cause of death in Iraq. The incidence of this cancer has increased sharply after the invasion of Iraq in 2003. Aim: To estimate immunohistochemical expression of vascular endothelial growth factor (VEGF) in CRC in relation to other parameters, such as grade and stage of tumour. Methods: Formalin fixed, paraffin-embedded blocks from 52 patients (27 male and 25 female) with CRC were included in this study. A group of 22 patients with non-cancerous colonic tissues were included as a control group. Avidin–biotin complex method was employed for immunohistochemical detection of VEGF. Results: VEGF immuno-expression was positive in 51.9% of CRC, while it was 18.2% in the normal colonic tissue (p<0.05). VEGF immunostaining was positively correlated with grade of colonic malignancy (p<0.05). Conclusion: These findings provide further evidence for the role of VEGF in the carcinogenesis of CRC. However, VEGF could not be well correlated with stage of tumour and hence may be a poor prognostic parameter of state of malignancy of colonic carcinoma.